PERBANDINGAN TEKANAN INTRAOKULAR LATIHAN BENCHPRESS DAN BICEPS MASS ROUTINE POLA PROGRESSIVE OVERLOAD - Dian Eka Saputra; Ardizal Rahman; Andrini Ariesti (HUMAN CARE JOURNAL, 2020)
Weight training as an isometric exercise can increase intraocular pressure (IOP) during exercise. Several mechanism theories are proposed in analyzing IOP elevation in weight training. Increased intra-abdominal pressure increases intracranial pressure thereby increasing IOP. Another theory is the Valsalva maneuver which results in an increase in intrathoracic venous pressure that is transmitted to the veins leading to the ocular so that IOP increases. IOP elevations over a period of time are at risk of causing glaucoma and blindness.Method: This study’s sample consisted of 62 students who were given biceps mass routine and benchpress training with 5 sets of progressive overload patterns. IOP values were measured before training, between sets and 30 minutes after rest using a non-contact tonometry.Result: There was a statistically significant correlation between the increase in IOP values between before exercise with the fifth set in the right eye lying position exercise (10.323mmHg) and the left eye (11.419mmHg) to the increase in the IOP value before exercise with the fifth set in the sitting position of the right eye ( 6,581mmHg) and left eye (7,435mmHg).Conclusion: IOP values increase during weight training at both positions of the progressive overload pattern. The greater the training load the greater the IOP value. The lying down position gives the effect of increasing the greater IOP value.